Pengaruh Kinerja Keuangan Terhadap Dana Insentif Fiskal pada Pemerintah Daerah Provinsi di Indonesia - Ades Hidayah; Sopiyan AR; Riana Mayasari (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to identify the factors that influence fiscal incentive funds in provincial local governments in Indonesia during the 2020-2022 period. The variables studied include fiscal incentive funds, regional financial independence ratio, regional spending efficiency ratio, and regional financial efficiency ratio. This study uses a quantitative method with a sample of 25 provinces selected using purposive sampling technique. The data collected is in the form of local government financial reports. The results showed that both partially and simultaneously, independent variables such as regional financial independence ratio, regional expenditure efficiency ratio, and regional financial efficiency ratio have an influence on fiscal incentive funds. These results are reinforced by literature studies which show that the independent variables in previous studies also have an effect on fiscal incentive funds.